Invasive barnacle fouling on an endemic burrowing crab mobile basibionts as vectors to invade a suboptimal habitat - Mendez, María Martha (2014)
Neohelice (Chasmagnathus) granulata is an ecosystem engineer endemic of salt marshes and mudflats of the southwestern Atlantic coast, where several Patagonian salt marshes were invaded by the acorn barnacle Balanus glandula, a typical rocky shore species. In this work, we supply the first report of the occurrence of epibiosis of B. glandula on N. granulata in these salt marshes and we describe the major ecological features of this invader/native association in order to generate sound baseline for further investigations and management decisions. Our results show that barnacles are found in the entire dorsal and lateral surface of the crabs, and specially in vital zones such us the basal insertion of the chelipeds, walking appendages, ocular peduncles, jaws, mouth with the carapace. Furthermore, the size reached by barnacles suggest that they are sexually mature and can reproduce while fouling on the crabs, being the maximum size of barnacles tightly associated and determined by the duration of the crab's inter-molt span. Our results highlight the mechanisms by which an invasive rocky shore invader can exploit an unfavorable environment (i.e. mobile substratum) to persist on soft bottom systems.